2011
DOI: 10.4097/kjae.2011.61.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protective effect by ulinastatin via an anti-inflammatory response after regional ischemia/reperfusion injury in an in vivo rat heart model

Abstract: BackgroundUlinastatin has anti-inflammatory properties and protects organs from ischemia/reperfusion-induced injury. The aim of this study was to investigate whether ulinastatin provides a protective effect on a regional myocardial ischemia/reperfusion injury in an in vivo rat heart model and to determine whether the anti-inflammatory response is related to its myocardial protective effect.MethodsRats were randomized to two groups. One group is received ulinastatin (50,000 U/kg or 100,000 U/kg) diluted in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…In another study, it was also able inhibit NF-κB activity and alleviate live ischemia reperfusion injury (18). Furthermore, it was demonstrated to decrease the expression of TNF-α, IL-6, caspase-3 and thus reduced lipopolysaccharide/d-gal-induced acute liver damage (13) and myocardial ischemia reperfusion injury (14). A previous study by our group demonstrated that UTI improves renal fibrosis (19); however, the mechanism underlying this effect remained elusive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, it was also able inhibit NF-κB activity and alleviate live ischemia reperfusion injury (18). Furthermore, it was demonstrated to decrease the expression of TNF-α, IL-6, caspase-3 and thus reduced lipopolysaccharide/d-gal-induced acute liver damage (13) and myocardial ischemia reperfusion injury (14). A previous study by our group demonstrated that UTI improves renal fibrosis (19); however, the mechanism underlying this effect remained elusive.…”
Section: Discussionmentioning
confidence: 98%
“…Total (Cu-Zn and Mn) SOD (EC 1.15.1.1) activity was determined according to the method described by Shin et al (14). The principle of the method is based on the inhibition of nitroblue tetrazolium (NBT) reduction by the xanthine-xanthine oxidase system as a superoxide generator.…”
Section: Assessment Of Oxidative Stress [Lipid Peroxidation (Mda) Andmentioning
confidence: 99%
“…Again, ulinastatin might have beneficial effects for relatively young and mildly ill patients, based on previous studies 5, 10, 13. Several animal and human studies reported that ulinastatin could have an organ‐protective effect 15, 29, 30. Hence, ulinastatin may work as “prevention” rather than “treatment” for organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…As the advantages of urinary protease inhibitors, ulinastatin (UTI), such as improving organs ischemia/reperfusion, and anti-inflammatory effects, it is widely used in cardiac protection under the conditions of cardiopulmonary resuscitation, heart failure and the others [1][2][3][4][5]. However, clinically, the myocardial protective effect of UTI is not obvious at low dosage level.…”
Section: Introductionmentioning
confidence: 99%